2012
DOI: 10.1097/scs.0b013e318240fe7f
|View full text |Cite
|
Sign up to set email alerts
|

Need for Revision Surgery After Alveolar Cleft Repair

Abstract: The study assessed the need for revision surgery and the relating factors in alveolar cleft autogenous bone grafting in patients with complete cleft. It was a retrospective study carried out in 2009. The medical records of the 54 patients with alveolar cleft who underwent autogenous bone grafting in the maxillofacial department in Shariati Hospital from 2005 to 2008 were studied. The patients' age, sex, cleft type, age at palatal and alveolar clefts repair, tooth missing, surgery turn, and presence of orthodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
2
24
0
1
Order By: Relevance
“…Our finding on postsurgical orthodontic treatment (Table 8) is consistent with a report suggesting that orthodontic space closure after grafting is linked to a lower level of graft resorption than orthodontic space openings (Schultze-Mosgau et al, 2003). Similarly, pre-or postsurgical orthodontic treatment was independently associated with lower need for revision after bone grafting (Shirani et al, 2012). Thus, post-SABG orthodontic movement of cleft-adjacent teeth can apply functional stress on the grafted bone and promote alveolar remodeling (Guidice et al, 2007;Shirani et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding on postsurgical orthodontic treatment (Table 8) is consistent with a report suggesting that orthodontic space closure after grafting is linked to a lower level of graft resorption than orthodontic space openings (Schultze-Mosgau et al, 2003). Similarly, pre-or postsurgical orthodontic treatment was independently associated with lower need for revision after bone grafting (Shirani et al, 2012). Thus, post-SABG orthodontic movement of cleft-adjacent teeth can apply functional stress on the grafted bone and promote alveolar remodeling (Guidice et al, 2007;Shirani et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, pre-or postsurgical orthodontic treatment was independently associated with lower need for revision after bone grafting (Shirani et al, 2012). Thus, post-SABG orthodontic movement of cleft-adjacent teeth can apply functional stress on the grafted bone and promote alveolar remodeling (Guidice et al, 2007;Shirani et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, despite reports of excellent long-term outcomes, the procedure is associated with donor site morbidity and the requirement for hospitalization due to pain in the graft donor site. In addition, graft resorption is well documented, and many studies have reported revision rates from 12 to 40% depending on cleft type (Goudy, Lott, Burton, Wheeler, & Canady, 2009;Montian Manosudprasit, Chaiyasang, & Chowchuen, 2011;Shirani, Abbasi, & Mohebbi, 2012) . Poor prognosis is more highly associated with patients that have wider or bilateral clefts.…”
Section: Alveolar Cleftsmentioning
confidence: 99%
“…11 Other studies have shown that the bone grafting at the mixed-dentition period is associated with a higher success rate. 12 In patients with a bilateral alveolar cleft in the mixed dentition, the teeth adjacent to the alveolar cleft are covered by a thin alveolar bone plate.…”
Section: Discussionmentioning
confidence: 99%